Pengaruh Model Problem Based Learning (PBL) terhadap Kemampuan Berpikir Kreatif Peserta Didik Pada Pembelajaran Biologi: Tinjauan Literatur - Rizal, Resti; Alberida, Heffi (Al-Alam: Islamic Science Education Journal, 2024)
Education in the current global era must be seen and oriented towards the development of 21st century competencies. The problem-based learning model is a learning model that involves students in solving problems and offers opportunities for students to learn things that more broadly focus on educating students to be active and responsible in all fields. So, in a lesson it is not only demanded that students are active, but also creative in solving all problems given by the teacher or problems found by the students themselves. Creative thinking is a skill and ability for students to understand a problem and find solutions to solving problems using different strategies or methods. The problem based learning model can be used to increase creative thinking in biology learning. A literature review of articles related to the topic of the seven year period (2016-2022) was used for research. It can be concluded that the application of the problem based learning model can be used as an effort to increase students' creative thinking in biology learning, because the 20 research results show that the application of the problem based learning model in biology learning can increase creative thinking.